Analysis of Mill Motor Speed on the Sugar Value in Bagasse Using the Fuzzy Logic Method at the Sugar Factory of PT. Pratama Nusantara Sakti - Ricky Rachman Nursa; Helmy Fitriawan; Sri Ratna Sulistiyanti (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
The Indonesian sugar industry faces a serious challenge in the form of low efficiency in sugarcane milling, which is indicated by the high pol value in bagasse. This condition indicates that a considerable amount of sugar remains trapped in the bagasse, resulting in sugar losses and reduced productivity. One of the operational factors contributing to this phenomenon is the rotational speed of the mill motor, as non-optimal speed can affect the level of juice extraction and the amount of sugar remaining in the bagasse. Therefore, this study aims to analyze the effect of mill motor rotational speed on the pol value of bagasse and to optimize this parameter using the fuzzy logic method. The fuzzy system was designed to process machine variables (motor speed and motor load) as well as supporting factors (moisture content, temperature, service life, and harvesting age) through inference rules based on membership functions. Results show that most fuzzy predictions are consistent with the actual data from the quality control division, with a high level of accuracy indicated by an RRMSE of 7.84%, MAE of 0.0603, and MAPE of 3.34%. These findings demonstrate that fuzzy logic is capable of handling uncertainty and the complexity of variables in the milling process, while also providing a practical solution to reduce sugar losses, improve quality, and enhance the productivity of the national sugar industry.